Effect of Edaravone on Favorable Outcome in Patients with Acute Cerebral Large Vessel Occlusion: Subanalysis of RESCUE-Japan Registry - MIYAJI, Yuki (Neurol Med Chir (Tokyo), 2015)
The data of the nationwide prospective registry of acute cerebral large vessel occlusion (LVO; RESCUE-Japan Registry) were analyzed to know the effect of edaravone, a free radical scavenger, on clinical outcome at 90 days after onset. In this registry, patients with acute cerebral LVO admitted within 24 h after onset were prospectively registered. The effect of various factors including endovascular treatment (EVT), intravenous recombinant tissue plasminogen activator (IV rt-PA), and other medication including edaravone on favorable outcome (modified Rankin scale 0–1) was analyzed. Of the 1,454 registered patients, 1,442 patients (99.2%) had the information of edaravone were analyzed. In total, edaravone group had more patients with favorable outcome compared to non-edaravone group (22.9% vs. 13.8%, p = 0.0006). Edaravone increased favorable outcome in patients treated with IV rt-PA (29.4% vs. 11.1%, p = 0.0107), but not with EVT (21.2% vs. 13.9%, p = 0.309). Logistic regression analysis revealed that higher National Institutes of Health Stroke Scale (NIHSS) score on admission [odds ratio (OR) 0.875, 95% confidence interval (CI) 0.858–0.894] and advanced age (OR 0.963, 95%CI 0.952–0.975) were significantly related to unfavorable outcome. In contrast, IV rt-PA (OR 2.489, 95%CI 1.867–3.319), EVT (OR 1.375, 95%CI 1.013–1.865), and edaravone (OR 1.483, 95%CI 1.027–2.143) were significantly associated with favorable outcome. This analysis indicated that IV rt-PA, EVT, and edaravone were effective to obtain favorable outcome in patients with acute LVO. Combination IV rt-PA with edaravone was more effective.